2018
DOI: 10.7554/elife.38621
|View full text |Cite
|
Sign up to set email alerts
|

CD95/Fas ligand mRNA is toxic to cells

Abstract: CD95/Fas ligand binds to the death receptor CD95 to induce apoptosis in sensitive cells. We previously reported that CD95L mRNA is enriched in sequences that, when converted to si/shRNAs, kill all cancer cells by targeting critical survival genes (Putzbach et al., 2017). We now report expression of full-length CD95L mRNA itself is highly toxic to cells and induces a similar form of cell death. We demonstrate that small (s)RNAs derived from CD95L are loaded into the RNA induced silencing complex (RISC) which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 38 publications
4
58
0
Order By: Relevance
“…To determine to what extent miR-K12-6-5p affects cell growth through 6mer seed toxicity, we performed a Metascape analysis comparing the gene ontologies of the enriched gene sets downregulated by miR-K12-6-5p with a number of stimuli we recently reported to kill cells in part through 6mer seed toxicity, including a CD95L-derived toxic siRNA , miR-34a-5p , miR-34a-5p 6seed , and the three genotoxic chemotherapeutic reagents doxorubicin, etoposide, and carboplatin ( Figure 3B). The genes that were downregulated in response to all these treatments had widely overlapping gene ontologies that were consistent with cells dying of 6mer seed toxicity Putzbach et al, 2017Putzbach et al, , 2018b. These data suggest that miR-K12-6-5p engages a cell death mechanism that is similar to the ones triggered by the other DISE-inducing reagents.…”
Section: Mir-k12-6-5p Predominantly Targets Essential Survival Genes mentioning
confidence: 56%
“…To determine to what extent miR-K12-6-5p affects cell growth through 6mer seed toxicity, we performed a Metascape analysis comparing the gene ontologies of the enriched gene sets downregulated by miR-K12-6-5p with a number of stimuli we recently reported to kill cells in part through 6mer seed toxicity, including a CD95L-derived toxic siRNA , miR-34a-5p , miR-34a-5p 6seed , and the three genotoxic chemotherapeutic reagents doxorubicin, etoposide, and carboplatin ( Figure 3B). The genes that were downregulated in response to all these treatments had widely overlapping gene ontologies that were consistent with cells dying of 6mer seed toxicity Putzbach et al, 2017Putzbach et al, , 2018b. These data suggest that miR-K12-6-5p engages a cell death mechanism that is similar to the ones triggered by the other DISE-inducing reagents.…”
Section: Mir-k12-6-5p Predominantly Targets Essential Survival Genes mentioning
confidence: 56%
“…To determine to what extent miR-K12-6-5p affects cell growth through 6mer seed toxicity, we performed a Metascape analysis comparing the gene ontologies of the enriched gene sets downregulated by miR-K12-6-5p and a number of stimuli we recently reported to kill cells in part through 6mer seed toxicity: a CD95L-derived toxic siRNA (Putzbach et al, 2017), miR-34a-5p , miR-34a-5p 6seed , and the three genotoxic chemotherapeutic reagents doxorubicin, etoposide and carboplatin ( Figure 3B). The genes that were downregulated in response to all these treatments had widely overlapping gene ontologies that were consistent with cells dying of 6mer seed toxicity Putzbach et al, 2017;Putzbach et al, 2018b). These data suggest that miR-K12-6-5p engages a cell death mechanism that is similar to the ones triggered by the other DISE inducing reagents.…”
Section: The Mir-15a/b-5p/16-5p Family Kills Cells In Part Through 6mmentioning
confidence: 55%
“…We found that 61% and >55%, respectively, of the genes that were downregulated in cells transfected with only the 6mer seed were also downregulated in the cells treated with the full miRNAs (Figure 1D, E). A gene ontology analysis revealed that the genes that were most downregulated grouped into GO terms that are consistent with cells dying from 6mer seed toxicity/DISE including mitosis, cell division, cell cycle regulation, and DNA replication Putzbach et al, 2017;Putzbach et al, 2018b) (Figure 1D, E). A gene set enrichment analysis confirmed that in all cases essential survival genes but not a control set of nonsurvival genes (as previously defined (Putzbach et al, 2017)) were downregulated with similar significance and enrichment scores ( Figure 1F).…”
Section: The Mir-15a/b-5p/16-5p Family Kills Cells In Part Through 6mmentioning
confidence: 99%
“…In support of this hypothesis, a previous report suggests that small RNAs derived from CD95L mRNA can be loaded into RISC and induce an endogenous DISE mechanism in cancer cells. Interestingly, secondary structure predictions indicate that CD95L mRNA forms a tightly folded structure with extensive regions of complementarity that could provide the endogenous double stranded sequences to be processed and loaded into RISC (Putzbach, Haluck-Kangas, et al, 2018). A similar prediction was obtained for the TMEFF2 mRNA (data not shown).…”
Section: Discussionmentioning
confidence: 99%